1997
DOI: 10.1002/jmri.1880070507
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive correction of imaging plane position in segmented K‐space cine cardiac MRI

Abstract: Variability among breath-holds frequently produces registration errors, a situation that may contribute to reproducibility error in anatomic indices. A navigator-echo-based method for real-time prospective correction of imaging slice level was applied to breath-hold cine cardiac imaging of 13 subjects. Repeat acquisitions with correction in the cardiac short-axis orientation showed significantly improved reproducibility in fractional area change and endocardial centroid location as compared with conventional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…In a previous study where a prospective navigator slice correction approach was used to compensate for differences of the diaphragmatic (and cardiac) position between serial breath-holds (Chuang et al, 1997), a significant underestimation of the LV EDV was found. While retrospective ECG-gating may allow decreasing the initial delay of the first phase from the QRS to a minimum, this is not applicable to prospectively ECGgated sequences that implement a trigger delay.…”
Section: Discussionmentioning
confidence: 93%
“…In a previous study where a prospective navigator slice correction approach was used to compensate for differences of the diaphragmatic (and cardiac) position between serial breath-holds (Chuang et al, 1997), a significant underestimation of the LV EDV was found. While retrospective ECG-gating may allow decreasing the initial delay of the first phase from the QRS to a minimum, this is not applicable to prospectively ECGgated sequences that implement a trigger delay.…”
Section: Discussionmentioning
confidence: 93%
“…In the in vivo part of this study, the measurements were taken at a location where the throughplane velocity-encoded measurements may be affected by cardiac and respiratory motion. Correction procedures have lately been proposed (22), and this could improve the accuracy of these measurements. However, this study focused on the precision of PVM.…”
Section: Discussionmentioning
confidence: 99%
“…Still, diaphragmatic drift during prolonged periods of sustained respiration has been reported [16] and could be a limiting factor. Hereby, the combination of C S P A M M myocardial tagging with prospective real-time navigator tracking could be a valuable enhancement [17] of the present methodology. However, this remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%